Redefining Language Education: A Hybrid Approach of Social Media and Conventional Teaching (International Journal of Scientific Research in Science and Technology, 2024)
In recent years, the influence of social media in English language platforms has significantly transformed the teaching and learning process. It made the educational path more flexible, innovative, immersive, interactive and experiential. Social media offers numerous opportunities, as well as challenges, for both educators and learners. In order to create engaging, real-world language learning experiences, it has become essential to rely on social media as a part of a digitally enhanced language learning process. Traditional and digital methods of language learning have their unique way of enhancing learners’ proficiency, co-existing both means of learning process can bring vast changes in the enhancement of language teaching and learning. The aim of this study is to rethink the way of language being taught inside the classroom based on the needs of the learners of this digital era. It highlights the benefits of blending digital and traditional methods in English language learning. It explores the ways in which social media can be integrated in language learning classrooms for an effective learning process. This paper tries to evaluate the necessity to depend on both traditional and digital methods of teaching and learning through quantitative analysis.